Spatial analyses of immune cell infiltration in cancer: current methods and future directions: A report of the International Immuno-Oncology Biomarker Working Group on Breast Cancer - Page, David; Broeckx, Glenn; Jahangir, Chowdhury Arif; Verbandt, Sara; Gupta, Rajarsi R.; Thagaard, Jeppe; Khiroya, Reena; Kos, Zuzana; Abduljabbar, Khalid; Acosta Haab, Gabriela; Acs, Balazs; Akturk, Guray; et al. (The journal of pathology, 2023)
Modern histologic imaging platforms coupled with machine learning methods have provided new opportunities to map the spatial distribution of immune cells in the tumor microenvironment. However, there exists no standardized method for describing or analyzing spatial immune cell data, and most reported spatial analyses are rudimentary. In this review, we provide an overview of two approaches for reporting and analyzing spatial data (raster versus vector-based). We then provide a compendium of spatial immune cell metrics that have been reported in the literature, summarizing prognostic associations in the context of a variety of cancers. We conclude by discussing two well-described clinical biomarkers, the breast cancer stromal tumor infiltrating lymphocytes score and the colon cancer Immunoscore, and describe investigative opportunities to improve clinical utility of these spatial biomarkers. © 2023 The Pathological Society of Great Britain and Ireland.
Online veröffentlicht: 23 August 2023
Gesehen am 30.01.2024